Cognitive Growth Model to Improve Problem Solving Ability and Activities of the Second Semester Students in Integral Calculus Course - Aprilia Nurul Chasanah; Arief Budi Wicaksono (Universitas Tidar, 2020)
The problem solving ability is needed for the students to be able to face the challenges of education on cognitive aspects. Meanwhile, in the affective aspect, the students’ activities also play an important role in the process of learning mathematics in higher education. Armed with activities and mathematical problem solving ability, they are expected to be more adaptive in their efforts to find solutions for each problem. The purpose of this research is to improve the activities and ability to solve mathematics problems in the second semester students in the Integral Calculus course using the Cognitive Growth model. This is a Classroom Action Research (CAR in the even semester 2018/2019). The subjects of this research are the second semester students of the Mathematics Education Study Program at a higher education institution in Magelang, Central Java, Indonesia. The data collection techniques in this research are the test, observation, and interview. The percentage for the aspect of the students’ activities in the first cycle = 51.51%, the second cycle = 58.56%, and the third cycle = 65.48%. The percentage of improvement in the students' mathematical problem solving ability in cycle I = 45.08%, cycle II = 40.08%, and cycle III = 56.59%. Therefore, it can be concluded that the application of the Cognitive Growth model can improve the activities and problem solving ability in the second semester students in the Integral Calculus course.